2018
DOI: 10.18805/ijare.a-321
|View full text |Cite
|
Sign up to set email alerts
|

Application of CSM–CERES–Rice in scheduling irrigation and simulating effect of drought stress on upland rice yield

Abstract: Crop models can provide rapid and cost effective means to deal with rice crop management. The objectives of this study included, exploring the ability of CSM-CERES-Rice in scheduling irrigation and to simulate the effect of drought stress on upland rice yield. Irrigation treatments 100, 70 and 50 % of field capacity (FC) were applied from 80 days after planting (DAP) at flowering stage until maturity and CSM-CERES-Rice was used to predict irrigation amount for each water regime for treatment duration. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 13 publications
4
20
0
Order By: Relevance
“…Hence, 28 °C had an adjustment excellent agreement for leaf area index with lower d-stat values among the three temperature stages for the genotypes. The result similar with the findings of Hussain et al (2018).…”
Section: Simulated Effect Of Temperatures On Leaf Area Index (Laid)supporting
confidence: 91%
See 2 more Smart Citations
“…Hence, 28 °C had an adjustment excellent agreement for leaf area index with lower d-stat values among the three temperature stages for the genotypes. The result similar with the findings of Hussain et al (2018).…”
Section: Simulated Effect Of Temperatures On Leaf Area Index (Laid)supporting
confidence: 91%
“…Measured mean tillers number = 56.45 (no/m 2 ) with nRMSE= 3.07 indicated that very excellent agreement with all the temperatures schedule and similar trend was followed by both the observed and simulated values for tillers number. This result is supported by Hussain et al (2018) representing tillers number response to grain yield, i.e., important yield contributing environmental factors.…”
Section: Simulated Effect Of Temperatures On Tillers Number (T#ad)mentioning
confidence: 59%
See 1 more Smart Citation
“…Our results indicate the impact of N fertilization and improvement in productivity with N fertilization according to various PDs. We have determined that the N fertilizer recommendations for upland rice production (DRRD, 2016 , 2017 ; Norsuwan et al, 2020 ) and N fertilizer application rate practiced in Thailand (CARSR, 2003 ; Hussain et al, 2018a , b ; Suwanasa et al, 2018 ; Islam et al, 2020 ) are not adequate. Another study conducted under partially controlled conditions in sheds also exhibited comparable results (Hussain et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In northern areas of Thailand, the application of 10–75 kg N ha −1 by farmers in upland rice fields was reported in a survey conducted by Chiang Mai University, Thailand (CARSR, 2003 ). Different NFRs have been observed as N fertilization of 61.25 kg N ha −1 (Suwanasa et al, 2018 ), 61.25 kg N ha −1 (Hussain et al, 2018a , b ), and a basal fertilization of 15 kg N ha −1 (Islam et al, 2020 ) in upland rice farming in southern Thailand. Corresponding to the Division of Rice Research and Development (DRRD) of Thailand (DRRD, 2016 ; Norsuwan et al, 2020 ), 48.75–82.5 kg N ha −1 based on soil N status was recommended to be used as N fertilization management for rice production.…”
Section: Introductionmentioning
confidence: 99%